Impact of HIV status and vaccination schedule on bacterial nasopharyngeal carriage following infant immunisation with the pneumococcal non-typeable Haemophilus influenzae protein D conjugate vaccine in South Africa. Issue 10 (28th February 2020) - Madhi, Shabir A.; Moreira, Marta; Koen, Anthonet; van Niekerk, Nadia; de Gouveia, Linda; Jose, Lisa; Cutland, Clare L.; François, Nancy; Schoonbroodt, Sonia; Ruiz-Guiñazú, Javier; Yarzabal, Juan Pablo; Borys, Dorota; et al.
Highlights: In our study, 484 South African infants were enrolled and vaccinated with PHiD-CV. HIV-infection or exposure did not alter PHiD-CV impact on bacterial carriage post-vaccination. Vaccine-type pneumococcal carriage tended to be lower in children receiving a PHiD-CV booster dose. Abstract: Background: Nasopharyngeal carriage (NPC) of Streptococcus pneumoniae is a precondition for pneumococcal disease and a source of transmission. This trial evaluated NPC of S. pneumoniae and other pathogens post-vaccination with the pneumococcal non-typeable Haemophilus influenzae (NTHi) protein D conjugate vaccine (PHiD-CV) in human immunodeficiency virus (HIV)-infected (HIV+), HIV-exposed-uninfected (HEU), and HIV-unexposed-uninfected (HUU) South African children. Methods: In this phase III, open, single‐centre, controlled study (ClinicalTrials.gov: NCT00829010), 484 children were stratified by HIV status: 83 HIV+, 101 HEU, and 300 HUU. HIV+ and HEU children received a 3 + 1 PHiD-CV vaccination schedule: primary vaccination, age 6/10/14 weeks, and booster dose, age 9–10 months. HUU infants were randomised (1:1:1) to 3-dose priming and booster (HUU/3+1); 3-dose priming without booster (HUU/3+0); or 2-dose priming and booster (HUU/2+1). Bacterial NPC was assessed 8 times up to 24–27 months of age. Results: Overall pneumococcal carriage rates were similar across 3+1 groups irrespective of HIV status; trends towards higher carriage rates in the HIV+ than HEU and HUU/3+1 groups were observed at 24–27 months of age. In HUU children, carriage of any pneumococcal serotype was similar for the three different dosing schedules at all timepoints; carriage of vaccine-type pneumococci tended to be lower at 16–19 months and 24–27 months of age in children who had received a booster dose (HUU/2+1 and HUU/3+1 groups) than in the HUU/3+0 group. Carriage rates of NTHi, Staphylococcus aureus and Moraxella catarrhalis were comparable between all groups. Conclusions: HIV infection or exposure did not seem to alter the effect of PHiD-CV on pneumococcal NPC in children during their first 2 years of life. NPC prevalence of vaccine-type pneumococci following vaccination series tended to be lower in children who had received a booster dose in comparison to those who had not.